Helicobacter pylori – risk factor of gastric cancer - BOTEZATU, Adriana (One Health & Risk Management, 2025)
Introduction. Over the last 7-8 decades, a global average annual percentage reduction of 2.1% in gastric cancer has been reported, partly due to the effective eradication and decreased prevalence of Helicobacter pylori infection, particularly among younger age cohorts, along with improved dietary habits and cancer screening. Material and methods. Publications were selected from the PubMed, Hinari, SpringerLink, and Google Search databases using the keyword “Helicobacter pylori” in various combinations with the terms “gastric cancer” and “carcinogenesis” to maximize the search yield. In the final bibliography, 36 representative articles were included for the purposes of this synthesis. Results. Inflammation is the most important and frequent factor in Helicobacter pylori-induced carcinogenesis. Chronic inflammation induces cancer by increasing the production of reactive oxygen species leading to oxidative stress, apoptosis of epithelial cells with a compensatory proliferative response of the remaining cells, and a higher risk of mutations in proliferating epithelial cells. In addition, Helicobacter pylori impairs DNA repair, causing epigenetic alterations in gastric epithelial cells. Conclusions. The pathogenesis of gastric cancer includes a sequence of events starting with Helicobacter pylori-induced chronic superficial gastritis, progressing to chronic atrophic gastritis, gastric intestinal metaplasia, gastric epithelial dysplasia, and ultimately gastric cancer.